Pengaruh DAR dan TATO terhadap ROA pada Perusahaan Subsektor Makanan dan Minuman di BEI Tahun 2014-2020 - Meita Pangestika; Ine Mayasari; Adang Kurniawan (Indonesian Journal of Economics and Management, 2021)
The research in this final project aims to determine the influence of Debt to Assets Ratio (DAR) and Total Assets Turnover (TATO) on Return on Assets (ROA) in food and beverage sub-sector companies listed on the IDX in 2014-2020. The type of data used in this study is panel data. The research method used is quantitative research. The test was carried out with panel data regression, classical assumption test, T Test (partial test), F Test (simultaneous test) and coefficient of determination. The results showed that partially Debt to Assets Ratio (DAR) had a negative and significant effect on Return on Assets (ROA), while Total Assets Turnover (TATO) had a positive and significant effect on Return on Assets (ROA). Simultaneously, Debt to Assets Ratio (DAR) and Total Assets Turnover (TATO) have a significant effect on Return on Assets (ROA) in food and beverage sub-sector companies listed on the IDX in 2014-2020.